A successful, highly complex and technical virtual training workshop in Ethiopia represented a milestone in what is now possible with remote learning - CGIAR Platform for Big Data in Agriculture (2021)
Successfully conducted a 4-day virtual training workshop with 20 Ethiopian participants from each of the MARPLE hubs in August 2021, held at ILRI-CIMMYT in Addis. Diane Saunders and Ashley Tuffin (JIC) led the workshop, guiding participants remotely through the entire MARPLE diagnostics pipeline.